2009
DOI: 10.1246/bcsj.82.277
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Removal of NO, NO2, and N2O by 146 nm Kr2 Excimer Lamp in N2 at Atmospheric Pressure

Abstract: The photochemical removal of NO, NO2, and N2O was investigated in N2 using a 146 nm Kr2 (25 mW cm−2) excimer lamp. The results obtained were compared with those obtained using 172 nm Xe2 (50 or 300 mW cm−2) excimer lamps. The removal rates of NO and NO2 at 146 nm were 11 and 36% slower than those at 172 nm, respectively. On the other hand, the removal rate of N2O at 146 nm was 21 times faster than that at 172 nm. The differences in the removal rates are discussed in terms of the absorption coefficient at each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The byproducts NO 2 – and SO 3 2– were not found in reaction solution. Besides, according to the results of Ye et al and Tsuji et al and the present results about SO 2 direct photolysis (as shown in Figure b), some elemental sulfur may be also produced in the reaction solution. However, it is difficult to determine its content because of its very low yield in the liquid phase and the complexity of the reaction solution.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…The byproducts NO 2 – and SO 3 2– were not found in reaction solution. Besides, according to the results of Ye et al and Tsuji et al and the present results about SO 2 direct photolysis (as shown in Figure b), some elemental sulfur may be also produced in the reaction solution. However, it is difficult to determine its content because of its very low yield in the liquid phase and the complexity of the reaction solution.…”
Section: Resultssupporting
confidence: 72%
“…According to the results of Tsuji’s studies and Ye et al, NO and SO 2 may be also directly decomposed by VUV light radiation according to following eqs –. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have inferred that VUV light irradiation may directly decompose SO 2 and NO by oxidation removal reactions . This assumption was verified by the experimental results of Tsuji, where they found the deposition of sulfur powders on the walls of the reaction chamber after photolysis of SO 2 in N 2 under VUV irradiation.…”
Section: Methodsmentioning
confidence: 99%